Geochemistry of Store Mosse Bog (SM) peat core from Sweden - Rixt de Jong; Svante Björck (PANGAEA, 2021)
Geochemistry data of a high-resolution peat core from the Past Global Changes - Carbon in Peat on EArth through Time (PAGES_C-PEAT) Project.